RANCANG BANGUN SISTEM REKOMENDASI PEMILIHAN APARTMENT DI BEKASI - Sari Wulanningsih Setio; Mira Febriana Sesunan (Jurnal Informatika, 2020)
Apartment is a building block which is divided into a number of spaces or units that are marketed on an intermediary or leased basis. Besides the location of the apartment is usually in the middle of the city close to various centers of activity (business,entertainment, health, education). So customers must come directly to the location of the apartment and compare one apartment with another apartment. This makes it difficult for many customers to make decisions in determining the choice of apartment in bekasi. Therefore this report uses the waterfall method which includes the analysis phase, the design phase, the implementation phase, the testing phase, the maintenance phase to complete the apartment selection.this study aims to design and build a decisionsupport system for apartment selection recommendations the reason that customers no longer need to come to the apartment one by one to ask the price, type, facilities with the system made easier to find an apartment as desired.The system implements by determining the criteria related to apartment search in bekasi which results in the customer being able to choose an apartment according to their desires that can be viewed based on the location of the apartment in bekasi.